POTENSI UMBI GANYONG DAN RUMPUT LAUT SEBAGAI BAHAN BAKU DALAM PEMBUATAN LASAGNA - Adhianata, Heni; Alberto, Marcellinus (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
Canna tuber (Canna discolour L.) is a source of carbohydrates and resistant starch (RS) related to its starch phosphate and amylose content. Meanwhile, seaweed (Eucheuma spinosum) is a type of hydrocolloid high in dietary fibre. This study aims to see the acceptability based on the results of organoleptic test and to evaluate the nutritional profile of lasagna made from canna tuber flour and seaweed flour. The raw materials used are canna tuber flour and seaweed flour with a ratio 60:40; 70:30; and 80:20 (w/w). The nutritional aspects observed included the levels of protein, fat, water, ash and dietary fibre. The result of the analysis showed that lasagna with a ratio of canna tuber flour: seaweed flour 70:30 (w/w) has the most favourable organoleptic properties. The result of the analysis of nutritional aspects of the sample also showed a significant increase in dietary fibre content (15.36%), ash content (1.25%), and lower fat content (0.16%) compared to commercial lasagna. Based on the result of this study, it can be concluded that canna tuber flour and seaweed flour have a potential as raw materials for lasagna production with favourable organoleptic properties and high dietary fibre content.